Cross cultural adaptation dimensions and demographic factors of international students in UUM - Najeemdeen, Iliyasu Shiyanbade (2017)
The number of international students in Malaysian universities have been increasing over the years. The international students come from many different countries and thus from a diverse cultural background. Thus, they had to adapt and adjust to the different cultural aspects of the Malaysian way of life. This study examined the differences between cross cultural adaptation dimensions and demographic factors (age, gender, marital status, study period and working experiences) that influence international students. A survey on 335 international students of Universiti Utara Malaysia was carried out to obtain the data for the study. The usable responses of 251 were analyze using SPSS version 22 involving descriptive statistic, anova and t-test. The result reveal there are no significant differences of age on cross cultural adaptation dimensions, but for gender, marital status, study period and work experience indicate significant differences for either one or two of the cross- cultural adaptation dimensions. This study revealed that there are many issues faced by the international students in UUM. The issues are related to the cross-cultural adaptation dimension and demographic factors among international students in UUM. Thus, it is recommended that there is a need to form an interaction among management and international students in the form of activities or programs to boost the cross-cultural adaptability of these students. This will enable the students to attain the necessary skills that will enhance their adaptability to the local context. Finally, implications, limitations of the study, and conclusion were also highlighted.